THE INFLUENCE OF TEACHER INNOVATION THROUGH STRENGTHENING PROACTIVE PERSONALITY, KNOWLEDGE SHARING, AND CREATIVE SELF-EFFICACY - Ade Setiadi Aulia; Soewarto Hardhienata; Herfina Herfina (Yayasan Education and Social Center, 2026)
This study aims to examine the direct and indirect effects of proactive personality (X1), knowledge sharing (X2), and creative self-efficacy (X3) on teacher innovation (Y) among vocational high school (SMK) teachers in Depok City, Indonesia. A quantitative approach was employed using path analysis with Partial Least Squares Structural Equation Modeling (PLS-SEM). Data were collected from 158 civil servant teachers across four public vocational high schools in Depok City using validated questionnaires. The study tested nine hypotheses examining both direct and indirect relationships. The results revealed that proactive personality (β = 0.212, p < 0.001), knowledge sharing (β = 0.229, p < 0.001), and creative self-efficacy (β = 0.205, p < 0.01) have significant positive direct effects on teacher innovation. Additionally, knowledge sharing and creative self-efficacy partially mediated the relationship between proactive personality and teacher innovation. The model explained 43.2% of the variance in teacher innovation. This study contributes to the educational management literature by empirically demonstrating the mediating mechanisms through which proactive personality influences teacher innovation. The findings provide practical implications for strengthening teacher innovation in vocational education contexts.